A method for rapidly assessing landslide hazard—taking the landslide in Yongxing town, Mingshan area as an example - He, Na; Gao, Xinhang; Zhong, Wei; Xu, Linjuan; Gurkalo, Filip (Frontiers in Earth Science, 2024)
To overcome the reliance on large samples and high-quality data in existing evaluation methods, while also improving evaluation efficiency and accuracy, this paper proposes a method for rapid landslide hazard assessment. This method utilizes existing research findings and specific analytical techniques for the study area to conduct rapid assessments.Taking the landslide in Yongxing Town, Mingshan Area, Ya'an City, Sichuan Province as an example,the Analytic Hierarchy Process (AHP) is combined with the the Information Value (IV) method, Certainty Factor (CF) method, and Frequency Ratio (FR) method from previous studies,The AHP-IV and AHP-FR methods assess the study area as a moderately hazardous zone, while the AHP-CF method assesses it as a slightly hazardous zone. Affected by the strong 2013 Lushan earthquake, the landslide in the study area caused permanent damage. Field investigation results show that the landslide hazard in the study area is moderate, and the AHP-IV and AHP-FR methods are more consistent with the actual field results. The AHP-CF method, due to not considering the water system factor and having certain errors in its discrimination method, leans towards a safer assessment, The results of the three evaluation methods are somewhat consistent.